Effects of Barrier Parameter to Stochastic Resonance Signal-to-noise Ratio in Feature Extraction - Tang Xuxiang; Ju Chunhua (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Effects of barrier parameter a to output signal-to-noise ratio (SNR) of bistable stochastic resonance in feature extraction was investigated in this paper. Barrier parameter a was changed with other systematic parameters fixed. The relationship between parameter aand the output SNR of non-linear stochastic resonance system was studied. This research provided us a novel way to extract the features using the non-linear stochastic resonance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3724